Penerapan Framework Ltsa Untuk Mengembangkan Lms Berbasis Blended Learning Untuk Proses Pembelajaran - Aflili Sari; Sarjon Defit; S Sumijan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Nowadays everyone is able to learn about anything, anywhere, and at any time because of the internet. Many schools have started implementing learning via E-learning. The development of E-learning as application software can be done using various methodologies or frameworks and one of them is the Learning Technology System Architecture (LTSA) framework which is standard 1484.1-2013 from the Institute of Electrical and Electronics Engineers (IEEE) for learning technology. This LTSA framework is applied with the aim of mapping the current and proposed systems, including mapping sub-systems and their relationships with external systems. The objectives to be achieved in this research include designing a Learning Management System at SMAN 2 Gunung Talang using the LTSA framework. Implementation of Blended Learning at SMAN 2 Gunung Talang by utilizing a Learning Management System designed with the LTSA framework to improve the quality of learning and Application of the LTSA framework to build a Learning Management System synchronized with learning at SMAN 2 Gunung Talang. There are 5 layers implemented in creating a Learning Management System using the LTSA framework. Layer 1: Learner interaction with the environment. Layer 2: The influence the learner has on the system. Layer 3: Component system. Layer 4: Identify stakeholder priorities and perspectives. Layer 5: Operational components and interoperability. The results of this research show that the existence of a Learning Management System based on the LTSA framework can create more focused, structured and well-archived learning at SMAN 2 Gunung Talang. The application of the LTSA framework in building a Learning Management System that is appropriate and in harmony with learning at SMAN 2 Gunung Talang has shown significant results in improving the quality of learning at SMAN 2 Gunung Talang.